On back with dedication to Vojtinskij. Umbreit left. Editorial staff of the Gewerkschaftszeitung of the Allgemeine Deutsche Gewerkschaftsbund
On back with dedication to Vojtinskij. Umbreit left. Editorial staff of the Gewerkschaftszeitung of the Allgemeine Deutsche Gewerkschaftsbund.